Serum Vitamin D Levels in Relation to Hypertension and Pre-hypertension in Adults: A Systematic Review and Dose–Response Meta-Analysis of Epidemiologic Studies - Mokhtari, Elahe; Hajhashemy, Zahra; Saneei, Parvane (Frontiers in Nutrition, 2022)
Background: Findings of observational studies that evaluated the association of serum vitamin D status and high blood pressure were contradictory. This meta-analysis of epidemiologic studies assessed the relation of serum vitamin D levels to hypertension (HTN) and pre-hypertension in adults. Methods: We conducted a systematic search of all published articles up to March 2021, in four electronic databases (MEDLINE (PubMed), Web of Science (ISI), Embase and Scopus) and Google scholar. Seventy epidemiologic studies (10 prospective cohort, one nested case-control and 59 cross-sectional investigations) that reported relative risks (RRs), odds ratios (ORs), hazard ratios (HRs) or prevalence ratios (PRs) with 95% confidence intervals (CIs) for HTN or pre-hypertension in relation to serum vitamin D concentrations in adults were included in the analysis. Results: In prospective studies, a 16% decrease in risk of hypertension was observed in participants with high levels of serum vitamin D compared to low levels (RR: 0.84; 95%CI: 0.73, 0.96; 12 effect sizes). Dose–response analysis in prospective studies revealed that each 25 nmol/L increase in serum vitamin D concentrations resulted in 5% reduced risk of HTN (RR: 0.95; 95% CI: 0.90, 1.00). Also, a significant nonlinear relationship between serum vitamin D levels and HTN was found (Pnonlinearity<0.001). In cross-sectional investigations, highest versus lowest level of serum vitamin D was related to reduced odds of HTN (OR: 0.84; 95%CI: 0.79, 0.90; 66 effect sizes) and pre-hypertension (OR: 0.75; 0.95%CI: 0.68, 0.83; 9 effect sizes). Dose-response analysis in these studies showed that each 25 nmol/L increase in serum vitamin D levels was related to a significant 6% reduction in odds of hypertension in all populations (RR: 0.94; 95%CI: 0.90, 0.99) and 3% in studies with representative populations (RR: 0.97; 95%CI: 0.95, 0.99). Conclusion: This meta-analysis of epidemiologic studies disclosed that serum vitamin D concentrations were inversely related to risk of hypertension in adults, in a dose–response manner in both prospective cohort and cross-sectional studies.